Crystal structure of tris(2-methyl-1H-imidazol-3-ium) benzene-1,3,5-tricarboxylate - Weronika Łukaszczyk; Allegra Lohse; Julia Leibing; Sudem Yildizbas; Irwana Rizvanovic; Simone Techert; Jose de Jesus Velazquez-Garcia (Acta Crystallographica Section E: Crystallographic Communications)
The structure of the title salt, 3C4H7N2+·C9H3O63− (1), is reported. The compound is formed with three 2-methylimidazolium cations and a fully deprotonated trimesic acid. The structure is disordered over two orientations, which were refined using a split model (90.99: 9.01occupancy ratio). Analysis of bond distances and angles reveals the differences and similarities between compound 1 and the previously published 2-methyl-1H-imidazol-3-ium 3,5-dicarboxybenzoate structure [Baletska et al., (2023). Acta Cryst. E79, 1088–1092] and tris(2-methyl-1H- imidazol-3-ium) 5-carboxybenzene-1,3-dicarboxylate 3,5-dicarboxybenzoate [Asprilla-Herrera et al. (2025). Acta Cryst. E81, 303–309], as well as the neutral counterparts of the ions [Tothadi et al. (2020). ACS Appl. Mater. Interfaces, 12, 15588–15594; Hachuła et al. (2010). J. Chem. Crystallogr. 40, 201–206]. The crystal packing analysis reveals the formation of hydrogen-bonded two-dimensional networks perpendicular to the [111] vector, where neighbouring planes interact via extensive π–π stacking.